Association Between Neutrophil-to-Lymphocyte Ratio (NLR) and Dengue Severity in Patients Treated at Bethesda Hospital, Yogyakarta - Jingan, Forensius; Christiane Marlene Sooai; Loury Priskila; Pradita Sri Mitasari; Wiwiek Probowati; Priskila, Loury (MEDICINUS, 2025)
Background: Dengue fever, a mosquito borne viral infection, remains a major public health concern in Indonesia, with the challenges in early identification of severe cases. The neutrophil-to-lymphocyte ratio (NLR) has emerged as a potentialbiomarker for assessing the disease severity.Objective: This study aimed to investigate the association between NLR and dengue severity in patients treated at Bethesda Hospital, Yogyakarta.Methods: A cross-sectional, quantitative study was conducted using medical record data from dengue patients admitted between 2022 to 2024. The NLR values were calculated from complete blood count results and disease severity was classified according to WHO guidelines. Statistical analysis was performed using the chi-square test and Fisher’s exact test.Results: Among the 68 patient samples, a significant association was found between NLR and dengue severity (p<0.001). Patients with lower NLR values were more likely to develop dengue hemorrhagic fever (DHF) compared to those with higher NLR values.Conclusion: The NLR plays a role in determining the severity of dengue infection and may serve as a predictive biomarker. This examination can be a practical tool in the clinical management of dengue fever patients, particularly for early detectionand optimizing therapeutic decision-making.